Impact of irregular tooth pitch of circular saw blades on power for wood cross-cutting : Utjecaj promjenjivog koraka zubi kružnih pila na snagu za poprečno rezanje drva - Krilek, Jozef (Array, 2020)
The article deals with the influence of irregular tooth pitch on energy consumption of cross-cutting wood. In this article, the effect was assessed of feeding velocity and parameters of saw blade on the cutting power Pc of spruce (Picea Abies), pine (Pinus Sylvestris) and beech (Fagus Silvatica) wood during sawing with a guided circular saw. For the research, two types of circular saw blades were used, one of them having irregular tooth pitch. The circular saw blades had sintered carbide inserts with a diameter of D = 350 mm and the same number of teeth. The feed velocities were vf = 4, 8,12 m∙min-1 and revolutions n = 3000 min-1. The results showed that the circular saw blades with irregular tooth pitch have higher energy consumption than the circular saw blades with regular tooth pitch. The highest cutting power Pc was shown in the case of beech. It was also shown that energy consumption is increasing linearly with increasing feed velocity.